Using routinely collected data to improve immunisation histories. Issue 2 (6th December 2013) - Allen, Luke
Abstract: Immunisation is one of the most effective health interventions in existence yet outbreaks of vaccine-preventable diseases continue to occur in developed countries. High rates of cover are needed to provide adequate herd immunity and there is evidence that a significant proportion of paediatric inpatients are not up to date even in areas with high levels of community cover. A proportion of these children will have parents who consciously declined immunisation, however the remaining children represent a vulnerable cohort whose under-immunisation is not routinely identified. Two-hundred consecutive admissions to rural paediatric assessment unit had their routinely documented vaccination histories checked against their records on the regional Child Health Information System (CHIS). 30 children (15%) were not up to date on the CHIS, yet routine clerking only identified 5 of these children (17%). After introduction of a simple system whereby ward clerks and doctors were taught how to access and print full immunisation histories from the CHIS, a further 200 consecutive admissions were audited. A similar number were not up to date (29/200) but the proportion of children with missing immunisations correctly identified in the clerking documentation increased to 52% (15 children). This is a 35% improvement (95% CI; 12-58%). Access to routinely collected data can significantly improve identification of under-immunised children and contribute towards higher levels of individual and herd-immunity.